Ammonia-alkali white mud admixture and preparation method

CN122916478APending Publication Date: 2026-10-16TANGSHAN SANYOU CHEM IND +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611128044.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

堆存过程中,白泥表面风化易产生扬尘污染,可溶性组分经淋滤渗入地下水和土壤,引发二次污染;若采用排海处理,还会破坏海洋生态环境、阻塞航道

Benefits of technology

(1)本发明通过对氨碱白泥掺合料中各成分进行合理设计,不仅破坏了氨碱白泥的惰性结构,提升了氨碱白泥掺合料活性,还通过与活化组分的复配,实现了对不同条件下氨碱白泥的水化活性、流动比和凝结时间进行了定向调节;特别地,针对上述单一性能指标或多性能指标不达标的应用场景,本发明明确了活化组分的具体种类及掺量值,从而实现了性能的靶向优化,显著提升了氨碱白泥掺合料的性能指标。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the technical field of industrial solid waste resource utilization, and particularly discloses an ammonia-alkali white mud admixture and a preparation method thereof. The ammonia-alkali white mud admixture comprises ammonia-alkali white mud, an activation component, a modifier, a grinding aid and a water-retention enhancer; the activation component comprises at least one of slag powder, fly ash microbead, silica ash or desulfurization gypsum; the modifier comprises A component and B component, the A component comprises at least one of aluminum hydroxide, metakaolin or zeolite powder, and the B component comprises tricalcium aluminate and triisopropanolamine; the grinding aid comprises triethanolamine, ethylene glycol, sodium lignosulfonate and a polycarboxylate superplasticizer; and the water-retention enhancer comprises nano-attapulgite, hydroxypropyl methyl cellulose ether and sodium carboxymethyl cellulose. The ammonia-alkali white mud admixture is optimized, the content is increased, the chloride ion permeability is effectively reduced, the construction and workability and the strength and stability are improved, and the service life of the concrete is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of industrial solid waste resource utilization technology, and in particular to an ammonia-alkali white mud admixture and its preparation method. Background Technology

[0002] The ammonia-soda process for producing soda ash generates ammonia-soda sludge, whose main components are calcium carbonate, calcium sulfate, calcium chloride, sodium chloride, calcium oxide, and small amounts of silicon, aluminum, and magnesium oxides. It has a pH value as high as 10.0~12.0, making it a highly alkaline solid waste. It is also fine-grained, highly absorbent, and easily deliquescent, and contains a certain amount of soluble chloride salts and impurities.

[0003] Currently, the main methods for treating ammonia-soda sludge are stockpiling and landfilling, with a small amount used in low-value-added fields such as soil conditioning and brick making. During stockpiling, the weathering of the sludge surface easily generates dust pollution, and soluble components leach into groundwater and soil, causing secondary pollution. If discharged into the sea, it will also damage the marine ecosystem and block shipping lanes. These disposal problems of ammonia-soda sludge not only occupy a large amount of land resources but also restrict the sustainable development of soda ash enterprises, becoming a major technical challenge and safety hazard in ammonia-soda process production.

[0004] While there have been attempts to use ammonia-alkali sludge as an admixture in cement and concrete production, existing technologies suffer from the following key drawbacks: First, ammonia-alkali sludge has a high content of soluble chloride salts (such as calcium chloride or sodium chloride), which, when directly added, can lead to steel corrosion and reduced concrete strength, affecting the durability of building materials. Second, ammonia-alkali sludge has low activity and an unreasonable particle size distribution, resulting in poor compatibility with cement and aggregates. Its addition reduces the cohesiveness and water retention of cement paste, easily causing problems such as bleeding and cracking. Third, impurities in ammonia-alkali sludge are not effectively removed, and its activity is not improved through proper compounding, leading to unstable admixture quality and limited dosage, typically not exceeding 5%, making large-scale resource utilization of ammonia-alkali sludge impossible. Fourth, some treatment methods suffer from high costs, complex processes, and immature technology, hindering industrial-scale promotion.

[0005] Therefore, developing a high-quality admixture for ammonia-alkali white mud that can effectively remove harmful impurities, improve its activity and compatibility, and has a simple preparation process, low cost, and can be produced on a large scale industrially has become an urgent technical problem to be solved. Summary of the Invention

[0006] In view of this, the present invention provides an ammonia-alkali white mud admixture and its preparation method.

[0007] To solve the above-mentioned technical problems, the technical solution provided by the present invention is as follows: This invention provides an ammonia-alkali white mud admixture, comprising the following raw material components in parts by weight: 100 parts ammonia-alkali white mud, 0-50 parts activating component, 2-8 parts modifier, 0.1-0.3 parts grinding aid, and 5-15 parts water retention enhancer; The activating component includes at least one of slag powder, fly ash microspheres, silica fume, or desulfurized gypsum; the modifier includes component A and component B, wherein component A includes at least one of aluminum hydroxide, metakaolin, or zeolite powder, and component B includes tricalcium aluminate and triisopropanolamine; the grinding aid includes triethanolamine, ethylene glycol, sodium lignosulfonate, and polycarboxylic acid superplasticizer; and the water-retaining and reinforcing agent includes nano-attapulgite, hydroxypropyl methylcellulose ether, and sodium carboxymethyl cellulose.

[0008] Compared to existing technologies, the ammonia-alkali white mud admixture provided by this invention contains activated alumina and silica in its activating components, namely slag powder and silica, which can supplement the hydration activity of the ammonia-alkali white mud admixture and improve its cementitious strength. Fly ash can reduce the water demand of the ammonia-alkali white mud admixture system and optimize powder flowability. Desulfurized gypsum can regulate the hydration and setting time of the ammonia-alkali white mud admixture and simultaneously produce a micro-expansion effect, compensating for the drying shrinkage deformation of concrete. By optimizing the composition of the activating components, this invention significantly improves the strength and durability of concrete when used as an ammonia-alkali white mud admixture in concrete.

[0009] The modifier A component provided by this invention contains active alumina and silica, which can undergo a secondary hydration reaction with calcium hydroxide and calcium carbonate in ammonia-alkali mud to generate C-(A)-SH gel and hydration products such as hydrated calcium aluminate. Meanwhile, tricalcium aluminate in modifier B component can rapidly participate in the hydration reaction, and triisopropanolamine has a dispersing effect, effectively compensating for the insufficient activity of ammonia-alkali mud and improving the cementitious strength of the ammonia-alkali mud admixture. The modifier provided by this invention can precisely adjust the alkalinity and ion release rate of the cementitious system, solving problems such as abnormal setting and rapid slump loss caused by poor compatibility between ammonia-alkali mud and cement systems, ensuring the workability and proportion stability of concrete mixing. Furthermore, the ion fixation effect of zeolite powder in the modifier, and the solidification effect of the aluminate system combining with chloride ions to form calcium chloroaluminate, can inhibit the re-adsorption and migration of residual chloride ions in ammonia-alkali mud, significantly reducing chloride ion permeability, while optimizing workability and strength stability, achieving a significant improvement in concrete durability.

[0010] Triethanolamine, ethylene glycol, sodium lignosulfonate, and polycarboxylate superplasticizers, used as grinding aids, not only optimize the performance of ammonia-alkali white mud admixtures but also improve concrete quality. Specific grinding aids effectively reduce the surface energy of particles in the ammonia-alkali white mud admixture, reducing particle adhesion and agglomeration, significantly improving grinding efficiency, and achieving refined particle control. Simultaneously, the grinding aids and activating components provided by this invention synergistically enhance the micro-aggregate filling effect of the ammonia-alkali white mud admixture, solving the problem of abnormally high concrete water demand caused by ammonia-alkali white mud agglomeration. Furthermore, the polycarboxylate superplasticizer and sodium lignosulfonate in the grinding aid exert a synergistic water-reducing and plasticizing effect, ensuring uniform dispersion of the ammonia-alkali white mud admixture in the slurry and significantly enhancing the slurry's ability to encapsulate aggregates. These mechanisms, while suppressing segregation and reducing mixing water consumption, achieve synergistic optimization of concrete workability and homogeneity, significantly improving the strength and durability of concrete.

[0011] In the water-retaining and reinforcing agent provided by this invention, nano-attapulgite, hydroxypropyl methylcellulose ether, and sodium carboxymethyl cellulose construct a three-dimensional water-retaining network. The three components intertwine to form a stable spatial network structure, effectively locking in the mixing moisture and significantly improving the water retention and cohesiveness of the concrete paste. This improves the problem of thin concrete paste caused by the addition of ammonia-alkali white mud, effectively solving the problems of easy bleeding and cracking in concrete with high dosage of ammonia-alkali white mud, and significantly reducing problems such as bleeding, segregation, and bottoming out of concrete. In addition, the specific water-retaining and reinforcing agent system can also achieve slow release of moisture, reduce the humidity gradient between the inside and outside of the concrete, effectively inhibit early plastic shrinkage and drying shrinkage cracks in concrete, and thus ensure the structural integrity and durability of concrete. Nano-attapulgite fully utilizes its nano-filling effect, filling the capillary pores inside the concrete cement matrix, optimizing the matrix pore structure, significantly improving the density of the hardened concrete, enhancing its impermeability, carbonation resistance, and erosion resistance, and ultimately significantly improving the concrete's resistance to bleeding, segregation, and cracking, while simultaneously improving the overall density and long-term durability.

[0012] Preferably, the ammonia-alkali sludge has a pH of 8.0-9.5, a particle size of 30-80 μm, and contains ≥50% calcium carbonate and ≥5% calcium oxide.

[0013] More preferably, the ammonia-alkali white mud has a water content of ≤1.5% and a soluble chloride salt content of ≤0.05% (calculated as chloride ions).

[0014] Preferably, when at least one of the indicators in the ammonia-alkali white mud does not meet the requirements of initial setting time ratio ≤ 300%, hydration activity ≥ 60%, and fluidity ratio ≥ 95%, the activating component is 10 to 50 parts.

[0015] Preferably, when the initial setting time ratio of the ammonia-alkali white mud is ≤300%, the hydration activity is ≥60%, and the fluidity ratio is ≥95%, the activating component is 0 parts.

[0016] Preferably, when the hydration activity of the ammonia-alkali white mud is <60%, the initial setting time ratio is ≤300%, and the fluidity ratio is ≥95%, the activating component includes the following raw material components by mass percentage: 65%~85% slag powder and 15%~35% silica fume.

[0017] It should be further noted that the testing standard for the hydration activity of the ammonia-alkali white mud is GB / T 1596-2017.

[0018] More preferably, the slag powder contains ≥12% active alumina and has a specific surface area of ​​500~600 m². 2 / kg.

[0019] More preferably, the silica fume contains ≥90% active silica and has a specific surface area of ​​15000~25000 m². 2 / kg.

[0020] Preferably, when the initial setting time ratio of the ammonia-alkali sludge is >300%, the hydration activity is ≥60%, and the fluidity ratio is ≥95%, the activating component includes desulfurized gypsum.

[0021] It should be further noted that the testing standard for the initial setting time ratio of the ammonia-alkali white mud is GB / T 18046-2017.

[0022] More preferably, the desulfurized gypsum has an SO3 content of ≥40% and a specific surface area of ​​300~350m². 2 / kg.

[0023] Preferably, when the fluidity ratio of the ammonia-alkali white mud is <95%, the hydration activity is ≥60%, and the initial setting time ratio is ≤300%, the activating component includes fly ash microspheres.

[0024] It should be further noted that the test standard for the fluidity ratio of the ammonia-alkali white mud is GB / T 18046-2017.

[0025] More preferably, based on the mass of the fly ash microspheres as 100%, the fly ash microspheres comprise the following components by mass percentage: SiO2: 45%~60%, Al2O3: 20%~35%, Fe2O3: 2~7%, CaO: 3~10%, K2O: 1~5%, MgO: 0~6%, Na2O: 1~5%, and SO3: 0~8%.

[0026] More preferably, the fly ash microspheres have a fineness of 15~75μm.

[0027] Preferably, when the hydration activity of the ammonia-alkali white mud is <60%, the fluidity ratio is <95%, and the initial setting time ratio is ≤300%, the activated component, based on 100% by mass, includes 55%~70% slag powder and 30%~45% fly ash microspheres.

[0028] Preferably, when the initial setting time of the ammonia-alkali white mud is >300%, the hydration activity is <60%, and the fluidity ratio is ≥95%, the activated component, based on 100% by mass, includes 70%~80% slag powder and 20%~30% desulfurized gypsum.

[0029] Preferably, when the hydration activity of the ammonia-alkali white mud is ≥60%, the initial setting time ratio is >300%, and the fluidity ratio is <95%, the activated component, based on 100% by mass, includes 35%~50% fly ash microspheres and 50%~65% desulfurized gypsum.

[0030] Preferably, when the hydration activity of the ammonia-alkali white mud is <60%, the fluidity ratio is <95%, and the initial setting time ratio is >300%, the activated component, based on 100% by mass, includes 30%~45% slag powder, 10%~20% silica fume, 20%~30% fly ash microspheres, and 10%~30% desulfurized gypsum.

[0031] Preferably, the mass ratio of component A to component B is (2~3):1.

[0032] More preferably, the particle size of component A is 10~50μm.

[0033] More preferably, the particle size of component B is 10~50μm.

[0034] More preferably, the mass ratio of tricalcium aluminate to triisopropanolamine is 1:(1~2).

[0035] Preferably, the mass ratio of triethanolamine, ethylene glycol, sodium lignosulfonate and polycarboxylate superplasticizer in the grinding aid is (5~7):(3~5):(2~4):(1~2).

[0036] Preferably, the polycarboxylate superplasticizer is 540P purchased from Jiangsu Bote New Materials Co., Ltd.

[0037] Preferably, the mass ratio of nano-attapulgite, hydroxypropyl methylcellulose ether, and sodium carboxymethyl cellulose in the water-retaining and reinforcing agent is 3:(1~2):(0.5~1).

[0038] Preferably, the average particle size of the nano-attapulgite is 40~100nm.

[0039] This invention provides a method for preparing the above-mentioned ammonia-alkali white mud admixture, comprising the following steps: Step 1: Weigh each component according to the mass ratio, and mix the weighed ammonia-alkali white mud, activating component, modifier, grinding aid and water retention enhancer evenly to obtain a mixture. Step 2: Activate the mixture at 300~400℃ to obtain activated material; Step 3: Grind the activated material, pass it through a 400-mesh sieve, collect the undersize material, and obtain ammonia-alkali white mud admixture.

[0040] In the preparation method of ammonia-alkali white mud admixture provided by the present invention, specific activation treatment conditions allow the components in the ammonia-alkali white mud admixture to react fully, destroying the inert structure in the ammonia-alkali white mud and improving its activity. At the same time, it can also promote the full combination of modifier and ammonia-alkali white mud, and reduce the alkalinity of ammonia-alkali white mud admixture.

[0041] Preferably, in step 1, the conditions for uniform mixing include: a rotation speed of 200~300 r / min and a time of 15~25 min.

[0042] Preferably, in step 2, the activation treatment time is 1 to 2 hours.

[0043] More preferably, in step 2, the activation treatment also requires stirring at a rate of 90~180 r / min.

[0044] Preferably, in step 3, during the grinding process, the ball-to-material ratio is controlled to be (3~5):1, and the grinding time is 30~60 minutes.

[0045] Compared with the prior art, the present invention has the following advantages: (1) By rationally designing the components in the ammonia-alkali white mud admixture, this invention not only destroys the inert structure of the ammonia-alkali white mud and improves the activity of the ammonia-alkali white mud admixture, but also achieves targeted adjustment of the hydration activity, flow ratio and setting time of the ammonia-alkali white mud under different conditions through compounding with the activating components. In particular, for application scenarios where the above-mentioned single performance index or multiple performance indexes are not up to standard, this invention clarifies the specific types and dosage values ​​of the activating components, thereby achieving targeted optimization of performance and significantly improving the performance index of the ammonia-alkali white mud admixture.

[0046] (2) The present invention optimizes the particle size distribution and compatibility of ammonia-alkali white mud admixture, and adds water-retaining and reinforcing agents and grinding aids. The mixing uniformity of ammonia-alkali white mud admixture, cement and aggregate is significantly improved, effectively improving the cohesiveness and water retention of cement paste, and avoiding water bleeding and cracking in concrete. The ammonia-alkali white mud admixture provided by the present invention can be added to concrete at a dosage of 15-30%, which is significantly higher than the 5% or less of the prior art, realizing the large-scale resource utilization of ammonia-alkali white mud.

[0047] (3) The preparation process of the ammonia-alkali white mud admixture provided by the present invention is simple, without the need for complex equipment and high temperature and high pressure conditions, the power consumption is significantly reduced, and all raw materials are common industrial raw materials, with low cost, suitable for industrial mass production, while reducing the environmental pollution caused by the storage of ammonia-alkali white mud, thus having both economic and environmental benefits.

[0048] (4) The ammonia-alkali white mud admixture provided by the present invention has stable quality and excellent performance. It can be widely used in the production of building materials such as cement, concrete and mortar. It can replace some cement clinker, reduce the production cost of building materials, and improve the mechanical properties and durability of building materials. Detailed Implementation

[0049] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0050] In the embodiments and comparative examples of this invention, the polycarboxylate superplasticizer was purchased from Jiangsu Bote New Material Co., Ltd. as 540P; the content of active alumina in the slag powder was 15.6%, and the specific surface area was 558 m². 2 / kg; the active silica content in the silica fume is 94.2%, and the specific surface area is 20000 m². 2 / kg; the SO3 content in the desulfurized gypsum is 43%, and the specific surface area is 335m². 2 / kg; Fly ash microspheres comprise the following components by mass percentage: SiO2: 49.6%, Al2O3: 28.3%, Fe2O3: 6.5%, CaO: 4.2%, K2O: 1.3%, MgO: 1.5%, Na2O: 3.8%, and SO3: 4.8%; The fineness of the fly ash microspheres is 40~60μm.

[0051] Unless otherwise specified, the embodiments and raw materials involved in this invention are all commercially available products, or can be prepared by referring to existing technical preparation methods.

[0052] Example 1 This embodiment provides an ammonia-alkali white mud admixture, comprising the following raw material components in parts by weight: 100 parts ammonia-alkali white mud, 40 parts activating component, 6 parts modifier, 0.2 parts grinding aid, and 10 parts water retention enhancer; The ammonia-alkali white mud contains 54% calcium carbonate and 6.3% calcium oxide. It has a pH of 8.5, a particle size of 60-80 μm, a water content of 1.2%, and a soluble chloride salt content of 0.03% (based on chloride ions). After testing, the hydration activity of the ammonia-alkali white mud was 56%, the fluidity ratio was 98%, and the initial setting time ratio was 285%. Based on the mass of the activating components as 100%, the activating components included 70% slag powder and 30% silica fume. The modifier includes component A and component B in a mass ratio of 2:1. Component A is metakaolin, and component B is tricalcium aluminate and triisopropanolamine in a mass ratio of 1:1. The particle size of component A is 30~50μm, and the particle size of component B is 30~50μm. The grinding aids consist of triethanolamine, ethylene glycol, sodium lignosulfonate, and polycarboxylate superplasticizer in a mass ratio of 6:4:2:1. The water-retaining and reinforcing agent comprises nano-attapulgite, hydroxypropyl methylcellulose ether, and sodium carboxymethyl cellulose in a mass ratio of 3:1:1, with the nano-attapulgite having a particle size of 50~70nm.

[0053] This embodiment provides a method for preparing the above-mentioned ammonia-alkali white mud admixture, including the following steps: Step 1: Weigh each component according to the mass ratio, mix the weighed ammonia-alkali white mud, activating component, modifier, grinding aid and water retention enhancer, and stir at a speed of 250 r / min for 20 min to mix evenly to obtain the mixture. Step 2: Feed the mixture into the activation furnace, control the activation temperature at 350℃, and stir the mixture at a rate of 180r / min for 1.5h to obtain the activated material; Step 3: Grind the activated material. During grinding, control the ball-to-material ratio to be 4:1 and the grinding time to be 45 minutes. Pass the material through a 400-mesh sieve. Return the material on the sieve to the ball mill for re-grinding. Collect the material under the sieve to obtain ammonia-alkali white mud admixture.

[0054] Example 2 This embodiment provides an ammonia-alkali white mud admixture, comprising the following raw material components in parts by weight: 100 parts ammonia-alkali white mud, 50 parts activating component, 7 parts modifier, 0.2 parts grinding aid, and 12 parts water retention enhancer. The ammonia-alkali white mud contains 52% calcium carbonate and 5.5% calcium oxide. It has a pH of 9.2, a particle size of 60-80 μm, a water content of 0.9%, and a soluble chloride salt content of 0.03% (based on chloride ions). After testing, the initial setting time ratio of ammonia-alkali white mud was 325%, the hydration activity was 66%, the fluidity ratio was 97%, and the activating component included desulfurized gypsum. The modifier includes component A and component B in a mass ratio of 2.3:1. Component A is zeolite powder, and component B is tricalcium aluminate and triisopropanolamine in a mass ratio of 1:2. The particle size of component A is 20~40μm, and the particle size of component B is 30~50μm. The grinding aids consist of triethanolamine, ethylene glycol, sodium lignosulfonate, and polycarboxylate superplasticizer in a mass ratio of 7:3:3:2. The water-retaining and reinforcing agent comprises nano-attapulgite, hydroxypropyl methylcellulose ether, and sodium carboxymethyl cellulose in a mass ratio of 3:2:1, with the nano-attapulgite having a particle size of 60~80nm.

[0055] This embodiment provides a method for preparing the above-mentioned ammonia-alkali white mud admixture, including the following steps: Step 1: Weigh each component according to the mass ratio, mix the weighed ammonia-alkali white mud, activating component, modifier, grinding aid and water retention enhancer, and stir at a speed of 300 r / min for 15 min to mix evenly to obtain the mixture. Step 2: Feed the mixture into the activation furnace, control the activation temperature at 400℃, and stir the mixture at a rate of 100r / min for 1 hour to obtain the activated material; Step 3: Grind the activated material. During grinding, control the ball-to-material ratio to be 5:1 and the grinding time to be 30 minutes. Pass the material through a 400-mesh sieve. Return the material on the sieve to the ball mill for re-grinding. Collect the material under the sieve to obtain ammonia-alkali white mud admixture.

[0056] Example 3 This embodiment provides an ammonia-alkali white mud admixture, comprising the following raw material components in parts by weight: 100 parts ammonia-alkali white mud, 45 parts activating component, 5.4 parts modifier, 0.15 parts grinding aid, and 8 parts water retention enhancer; The ammonia-alkali white mud contains 56% calcium carbonate and 5.8% calcium oxide. It has a pH of 8.7, a particle size of 40-60 μm, a water content of 0.8%, and a soluble chloride salt content of 0.04% (based on chloride ions). After testing, the hydration activity of the ammonia-alkali white mud was 71%, the initial setting time ratio was 287%, the fluidity ratio was 90%, and the activating component included fly ash microspheres. The modifier includes component A and component B in a mass ratio of 2:1. Component A is aluminum hydroxide, and component B is tricalcium aluminate and triisopropanolamine in a mass ratio of 1:1. The particle size of component A is 20~40μm, and the particle size of component B is 10~30μm. The grinding aids consist of triethanolamine, ethylene glycol, sodium lignosulfonate, and polycarboxylate superplasticizer in a mass ratio of 5:5:3:2. The water-retaining and reinforcing agent comprises nano-attapulgite, hydroxypropyl methylcellulose ether, and sodium carboxymethyl cellulose in a mass ratio of 3:1:1, with the nano-attapulgite having a particle size of 50~70nm.

[0057] This embodiment provides a method for preparing the above-mentioned ammonia-alkali white mud admixture, including the following steps: Step 1: Weigh each component according to the mass ratio, mix the weighed ammonia-alkali white mud, activating component, modifier, grinding aid and water retention enhancer, and stir at a speed of 200 r / min for 25 min to mix evenly to obtain the mixture. Step 2: Feed the mixture into the activation furnace, control the activation temperature at 300℃, and stir the mixture at a rate of 120r / min for 2 hours to obtain the activated material; Step 3: Grind the activated material. During grinding, control the ball-to-material ratio to be 3:1 and the grinding time to be 60 minutes. Pass the material through a 400-mesh sieve. Return the material on the sieve to the ball mill for re-grinding. Collect the material under the sieve to obtain ammonia-alkali white mud admixture.

[0058] Example 4 This embodiment provides an ammonia-alkali white mud admixture, comprising the following raw material components in parts by weight: 100 parts ammonia-alkali white mud, 35 parts activating component, 6.3 parts modifier, 0.2 parts grinding aid, and 11 parts water retention enhancer; The ammonia-alkali white mud contains 58% calcium carbonate and 6.9% calcium oxide. It has a pH of 8.9, a particle size of 50-70 μm, a water content of 1.1%, and a soluble chloride salt content of 0.05% (based on chloride ions). After testing, the hydration activity of the ammonia-alkali white mud was 54%, the fluidity ratio was 90%, and the initial setting time ratio was 274%. Based on the mass of the activated components as 100%, the activated components included 70% slag powder and 30% fly ash microspheres. The modifier includes component A and component B in a mass ratio of 2:1. Component A is aluminum hydroxide, and component B is tricalcium aluminate and triisopropanolamine in a mass ratio of 1:2. The particle size of component A is 30~40μm, and the particle size of component B is 20~40μm. The grinding aids consist of triethanolamine, ethylene glycol, sodium lignosulfonate, and polycarboxylate superplasticizer in a mass ratio of 6:4:2:1. The water-retaining and reinforcing agent comprises nano-attapulgite, hydroxypropyl methylcellulose ether, and sodium carboxymethyl cellulose in a mass ratio of 3:1:1, with the nano-attapulgite having a particle size of 60-80 nm.

[0059] This embodiment provides a method for preparing the above-mentioned ammonia-alkali white mud admixture, including the following steps: Step 1: Weigh each component according to the mass ratio, mix the weighed ammonia-alkali white mud, activating component, modifier, grinding aid and water retention enhancer, and stir at a speed of 240 r / min for 20 min to mix evenly to obtain the mixture material; Step 2: Feed the mixture into the activation furnace, control the activation temperature at 330℃, and stir the mixture at a rate of 140r / min for 1.5h to obtain the activated material; Step 3: Grind the activated material. During grinding, control the ball-to-material ratio to be 3:1 and the grinding time to be 40 minutes. Pass the material through a 400-mesh sieve. Return the material on the sieve to the ball mill for re-grinding. Collect the material under the sieve to obtain ammonia-alkali white mud admixture.

[0060] Example 5 This embodiment provides an ammonia-alkali white mud admixture, which differs from Embodiment 1 in that the ammonia-alkali white mud contains 52% calcium carbonate, 5.5% calcium oxide, has a pH of 8.4, a particle size of 60-80 μm, a water content of 0.9%, and a soluble chloride salt content of 0.03% (based on chloride ions). After testing, when the hydration activity of the ammonia-alkali white mud was 53%, the fluidity ratio was 96%, and the initial setting time ratio was 308%, the activating component included the following raw material components by mass percentage: the activating component included 80% slag powder and 20% desulfurized gypsum; The other components and preparation methods are the same as in Example 1, and will not be repeated here.

[0061] Example 6 This embodiment provides an ammonia-alkali white mud admixture, which differs from Embodiment 1 in that the ammonia-alkali white mud contains 52% calcium carbonate, 5.5% calcium oxide, has a pH of 8.5, a particle size of 60-80 μm, a water content of 0.9%, and a soluble chloride salt content of 0.03% (based on chloride ions). After testing, the hydration activity of the ammonia-alkali white mud was 66%, the initial setting time ratio was 310%, and the fluidity ratio was 92%. Based on the mass of the activated components as 100%, the activated components included 40% fly ash microspheres and 60% desulfurized gypsum. The other components and preparation methods are the same as in Example 1, and will not be repeated here.

[0062] Example 7 This embodiment provides an ammonia-alkali white mud admixture, which differs from Embodiment 1 in that the ammonia-alkali white mud contains 52% calcium carbonate, 5.5% calcium oxide, has a pH of 9, a particle size of 60-80 μm, a water content of 0.9%, and a soluble chloride salt content of 0.03% (based on chloride ions). After testing, the initial setting time ratio of the ammonia-alkali white mud was 311%, the hydration activity was 55%, and the fluidity ratio was 90%. Based on the mass of the activated components as 100%, the activated components included 30% slag powder, 20% silica fume, 20% fly ash microspheres, and 30% desulfurized gypsum. The other components and preparation methods are the same as in Example 1, and will not be repeated here.

[0063] Example 8 This embodiment provides an ammonia-alkali white mud admixture, which differs from Embodiment 1 in that the initial setting time ratio of the ammonia-alkali white mud is 292%, the hydration activity is 61%, the fluidity ratio is 96%, and no activating components are added. The other components and preparation methods are the same as in Example 1, and will not be repeated here.

[0064] Example 9 This embodiment provides an ammonia-alkali white mud admixture, which differs from Embodiment 1 in that: The modifier consists of component A and component B in a mass ratio of 1:5; The other components and preparation methods are the same as in Example 1, and will not be repeated here.

[0065] Comparative Example 1 This comparative example provides an ammonia-alkali white mud admixture, which differs from Example 1 in that: both slag powder and silica fume are replaced with an equal amount of limestone powder, the activated component includes only limestone powder, the limestone powder contains 95% calcium carbonate and 5% other components, and has a particle size of 20~50μm. The other components and preparation methods are the same as in Example 1, and will not be repeated here.

[0066] Comparative Example 2 This comparative example provides an ammonia-alkali white mud admixture, which differs from Example 1 in that no modifier is added; The other components and preparation methods are the same as in Example 1, and will not be repeated here.

[0067] Comparative Example 3 This comparative example provides an ammonia-alkali white mud admixture, which differs from Example 1 in that the polycarboxylic acid superplasticizer in the grinding aid is replaced with an equal amount of sodium gluconate. The other components and preparation methods are the same as in Example 1, and will not be repeated here.

[0068] Comparative Example 4 This comparative example provides an ammonia-alkali white mud admixture, which differs from Example 1 in that it does not contain a water-retaining and reinforcing agent; The other components and preparation methods are the same as in Example 1, and will not be repeated here.

[0069] Comparative Example 5 This comparative example provides an ammonia-alkali white mud admixture, which differs from Example 1 in that: the nano-attapulgite clay in the water-retaining and reinforcing agent is replaced with an equal amount of heavy calcium carbonate powder, the heavy calcium carbonate powder having a calcium carbonate content of 98.5% and a particle size of 5~30μm; The other components and preparation methods are the same as in Example 1, and will not be repeated here.

[0070] Example of effect The ammonia-alkali white mud admixtures provided in the embodiments and comparative examples of the present invention were tested, then applied to concrete, and the concrete performance was tested. The specific test indicators and test methods are as follows: Admixtures: Hydration activity was tested according to GB / T 1596-2017; initial setting time ratio and fluidity ratio were tested according to GB / T18046-2017.

[0071] Concrete: Mix ammonia-alkali white mud admixture with cement to prepare ammonia-alkali white mud admixture C30 concrete according to JGJ 55-2011; replace the above ammonia-alkali white mud admixture with an equal amount of S95 mineral powder admixture to prepare S95 mineral powder admixture concrete. The compressive strength of concrete shall be tested in accordance with GB / T 50081-2019; the workability shall be tested in accordance with GB / T 50080-2016; and the chloride ion permeability coefficient shall be tested in accordance with GB / T 50082-2024. The calculation method for the 28-day compressive strength change rate is as follows: 28d compressive strength change rate (%) = (28d compressive strength of S95 mineral powder admixture concrete - 28d compressive strength of ammonia-alkali white mud admixture C30 concrete) / 28d compressive strength of ammonia-alkali white mud admixture C30 concrete × 100; The method for calculating the rate of change of chloride ion permeability is as follows: Chloride ion permeability coefficient change rate (%) = (chloride ion permeability coefficient of S95 mineral powder admixture concrete - chloride ion permeability coefficient of ammonia-alkali white mud admixture C30 concrete) / chloride ion permeability coefficient of ammonia-alkali white mud admixture C30 concrete × 100.

[0072] The specific test results are shown in Tables 1 and 2.

[0073] Table 1. Test results of admixtures Table 2 Concrete test results The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A kind of ammonia-alkali white mud admixture, characterized in that, The raw material components include the following parts by weight: 100 parts of ammonia-alkali white mud, 0-50 parts of activating component, 2-8 parts of modifier, 0.1-0.3 parts of grinding aid and 5-15 parts of water retention enhancer; The activating component includes at least one of slag powder, fly ash microspheres, silica fume, or desulfurized gypsum; the modifier includes component A and component B, wherein component A includes at least one of aluminum hydroxide, metakaolin, or zeolite powder, and component B includes tricalcium aluminate and triisopropanolamine; the grinding aid includes triethanolamine, ethylene glycol, sodium lignosulfonate, and polycarboxylic acid superplasticizer; and the water-retaining and reinforcing agent includes nano-attapulgite, hydroxypropyl methylcellulose ether, and sodium carboxymethyl cellulose.

2. The ammonia-alkali white mud admixture as described in claim 1, characterized in that, The ammonia-alkali sludge has a pH of 8.0-9.5, a particle size of 30-80 μm, and contains ≥50% calcium carbonate and ≥5% calcium oxide. The ammonia-alkali white mud has a water content of ≤1.5% and a soluble chloride salt content of ≤0.05% (calculated as chloride ions).

3. The ammonia-alkali white mud admixture as described in claim 1, characterized in that, When at least one of the indicators in the ammonia-alkali white mud does not meet the requirements of initial setting time ratio ≤300%, hydration activity ≥60%, and fluidity ratio ≥95%, the activating component is 10~50 parts; When the initial setting time ratio of the ammonia-alkali white mud is ≤300%, the hydration activity is ≥60%, and the fluidity ratio is ≥95%, the activation component is 0 parts. When the hydration activity of the ammonia-alkali white mud is <60%, the initial setting time ratio is ≤300%, and the fluidity ratio is ≥95%, the activating component includes the following raw material components by mass percentage: 65%~85% slag powder and 15%~35% silica fume; When the initial setting time ratio of the ammonia-alkali white mud is >300%, the hydration activity is ≥60%, and the fluidity ratio is ≥95%, the activating component includes desulfurized gypsum. When the fluidity ratio of the ammonia-alkali white mud is <95%, the hydration activity is ≥60%, and the initial setting time ratio is ≤300%, the activating component includes fly ash microspheres.

4. The ammonia-alkali white mud admixture as described in claim 1, characterized in that, When the hydration activity of the ammonia-alkali white mud is <60%, the fluidity ratio is <95%, and the initial setting time ratio is ≤300%, the activated component, based on 100% by mass, comprises 55%~70% slag powder and 30%~45% fly ash microspheres; When the initial setting time ratio of the ammonia-alkali white mud is >300%, the hydration activity is <60%, and the fluidity ratio is ≥95%, the activated component, based on 100% by mass, comprises 70%~80% slag powder and 20%~30% desulfurized gypsum. When the hydration activity of the ammonia-alkali white mud is ≥60%, the initial setting time ratio is >300%, and the fluidity ratio is <95%, the activated component, based on 100% by mass, comprises 35%~50% fly ash microspheres and 50%~65% desulfurized gypsum; When the hydration activity of the ammonia-alkali white mud is <60%, the fluidity ratio is <95%, and the initial setting time ratio is >300%, the activated component, based on 100% by mass, includes 30%~45% slag powder, 10%~20% silica fume, 20%~30% fly ash microspheres, and 10%~30% desulfurized gypsum.

5. The ammonia-alkali white mud admixture as described in claim 3 or 4, characterized in that, The slag powder contains ≥12% active alumina and has a specific surface area of ​​500~600 m². 2 / kg; The silica fume contains ≥90% active silica and has a specific surface area of ​​15000~25000 m². 2 / kg; The desulfurized gypsum has an SO3 content of ≥40% and a specific surface area of ​​300~350m². 2 / kg; Based on the mass of the fly ash microspheres as 100%, the fly ash microspheres comprise the following components by mass percentage: SiO2: 45%~60%, Al2O3: 20%~35%, Fe2O3: 2~7%, CaO: 3~10%, K2O: 1~5%, MgO: 0~6%, Na2O: 1~5%, and SO3: 0~8%; The fly ash microspheres have a fineness of 15~75μm.

6. The ammonia-alkali white mud admixture as described in claim 1, characterized in that, The mass ratio of component A to component B is (2~3):

1.

7. The ammonia-alkali white mud admixture as described in claim 1 or 6, characterized in that, The mass ratio of tricalcium aluminate to triisopropanolamine is 1:(1~2). The particle size of component A is 10~50μm; The particle size of component B is 10~50μm.

8. The ammonia-alkali white mud admixture as described in claim 1, characterized in that, The mass ratio of triethanolamine, ethylene glycol, sodium lignosulfonate and polycarboxylate superplasticizer in the grinding aid is (5~7):(3~5):(2~4):(1~2); The mass ratio of nano-attapulgite, hydroxypropyl methylcellulose ether, and sodium carboxymethyl cellulose in the water-retaining and reinforcing agent is 3:(1~2):(0.5~1).

9. A method for preparing the ammonia-alkali white mud admixture according to any one of claims 1 to 8, characterized in that, Includes the following steps: Step 1: Weigh each component according to the mass ratio, and mix the weighed ammonia-alkali white mud, activating component, modifier, grinding aid and water retention enhancer evenly to obtain a mixture. Step 2: Activate the mixture at 300~400℃ to obtain activated material; Step 3: Grind the activated material, pass it through a 400-mesh sieve, collect the undersize material, and obtain ammonia-alkali white mud admixture.

10. The method for preparing ammonia-alkali white mud admixture as described in claim 9, characterized in that, In step 2, the activation treatment time is 1 to 2 hours.